Pengaruh Pola Asuh terhadap Gaya Hidup Mahasiswa Rantau pada Program Studi Bimbingan dan Konseling Islam UIN FAS Bengkulu - Putri, Anggel Pames Lader; Fauziyyah, Ayu; Krisna, Dicka; Cahyani, Elya; Marhayati, Nelly (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Being a migrant is one of the characteristics of Indonesian society, but it turns out that parenting patterns brought from the area of origin sometimes affect a person's lifestyle, especially students when they migrate. The purpose of this study was to see the influence of parenting patterns on the lifestyle of Rantau students at UIN FAS Bengkulu. This study was conducted quantitatively with a sample of 66 students. The results showed that parenting patterns did not have a significant effect on the lifestyle of UIN FAS students. There are other influences, namely peers and social media.